2019
DOI: 10.3389/fnins.2019.01305
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Causes Hypertension in Rats Even Under Chemical Blockade of Peripheral Sympathetic Nerves

Abstract: Synthetic glucocorticoids (GCs) are widely used to treat inflammatory conditions. However, chronic use of GCs can lead to hypertension. The cause of this undesired side effect remains unclear. Previously, we developed an in vivo rat model to study the mechanisms underlying hypertension induced by the chronic administration of the potent synthetic GC, dexamethasone (DEX) and found that the catecholamine biosynthetic pathway plays an important role. In the current study, we used this model to investigate the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Besides, hypertensive patients, who are also at risk for COVID-19 severity, should be at constant monitoring during dexamethasone treatment, once GCs-induced hypertension is frequently observed (115). High dexamethasone doses are associated with increased sodium retention, which leads to the elevation of blood pressure, in addition to chemical alteration of peripheral nerves homeostasis (87,116,117). This effect could lead to complications rather than COVID-19 treatment, increasing the associated mortality risks of the affected individuals.…”
Section: Corticosteroid Dexamethasonementioning
confidence: 99%
“…Besides, hypertensive patients, who are also at risk for COVID-19 severity, should be at constant monitoring during dexamethasone treatment, once GCs-induced hypertension is frequently observed (115). High dexamethasone doses are associated with increased sodium retention, which leads to the elevation of blood pressure, in addition to chemical alteration of peripheral nerves homeostasis (87,116,117). This effect could lead to complications rather than COVID-19 treatment, increasing the associated mortality risks of the affected individuals.…”
Section: Corticosteroid Dexamethasonementioning
confidence: 99%
“…Although some studies showed the positive effects of glucocorticoids on the contractile performance of the heart, [8,10] these effects might depend on the dose and the treatment duration. [11,12] Glucocorticoid treatment in the short-term with low doses has positive effects such as an increase in cardiac functions, and a decrease in inflammation; however, chronic glucocorticoid treatment causes hypertension, [13] left ventricular atrophy, cardiac fibrosis. [11] Previous studies of chronic treatment of glucocorticoids also contribute to the development of fibrosis, heart failure, and cardiac arrest.…”
Section: Glucocorticoids and Cardiac Remodeling Mechanismsmentioning
confidence: 99%
“…[11] Previous studies of chronic treatment of glucocorticoids also contribute to the development of fibrosis, heart failure, and cardiac arrest. [4,9,13,37,38] However, the mechanism linking glucocorticoid-induced insulin resistance in cardiovascular disease are not well elucidated.…”
Section: Glucocorticoids and Cardiac Remodeling Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations